THE USE OF BIOCHAR AND VERMICOMPOST COMBINATION IN INCREASING THE GROWTH AND YIELD OF RED CHILI - Eliyant, Eliyanti; Zulkarnain, Zulkarnain; Ichwan, Budiyati; Mahbub, Itang Ahmad; Susilawati, Susilawati (LPPM Universitas Jambi, 2026)
This investigation aimed to study the response of chili to the application of biochar and vermicompost, and to find the combination that produced the best growth and yield of red chili. The trial was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi from May 2023 through to October 2023. The treatments tested were the application of five different soil ameliorant, i.e. 100% biochar, 75% biochar + 25% vermicompost, 50% biochar + 50% vermicompost, 25% biochar + 75% vermicompost, 100% vermicompost, and 100% NPK fertilizer. The experiment was arranged in a completely randomized block design with four replications each consisted of 14 plants (7 of them were taken as sample plants). The results showed that the application of biochar along with vermicompost could increase the growth and yield of red chili. The use of 25% biochar + 75% vermicompost resulted in the highest growth and yield, indicated by average fruit number of 58.75 per plant and fruit weight of 173.71 g per plant, or 6.95 ton·ha-1. Thus, our study proved that the application of biochar and vermicompost is crucial to improve drought-tolerance of red chili cultivated in dry land.